OWE-012 Nationwide population-based evaluation of mortality and cancer-risk in young patients with ulcerative colitis/primary sclerosing cholangitis. (8th June 2018) - Trivedi, Palak; Mytton, Jemma; Evison, Felicity; Kamarajah, Sivesh Kathir; Reece, Jessamy; Iqbal, Tariq; Cooney, Rachel; Thompson, Fiona; Walmsley, Martine; Ferguson, James; Hirschfield, Gideon
Abstract : Introduction: Advancing age is proposed as a risk factor for mortality in primary sclerosing cholangitis (PSC) (Trivedi*Weismuller* et al. Gastro. 2017). However outcomes against a matched control population need evaluation. Our aim was to provide data-driven prioritisation of unmet need by comparing pts. with ulcerative colitis (UC) and coexisting PSC vs an age-matched cohort with UC alone in a stratified outcomes' analysis. Method: A population-based study was performed via linkage to the national Hospital Episode Statistics registry, which records every adult (>18 y of age) hospital attendance, admission or clinic event within England since 2006. Across the entire registry we captured all incident cases of UC alone (group I); and UC with an established diagnosis of PSC, or UC diagnosed with PSC subsequently (group 2). Case finding/definition was as per Jess et al (Gastro 2012), by applying ICD10 codes for UC overall (inclusion K51), UC/PSC more specifically (inclusion K51 +K83.0) and excluding other causes of liver injury (K70–77, K80.3/4, B16–19). Cases were captured till 03/2015; follow-up ending 1y thereafter. Event rates (colectomy, colorectal cancer [CRC], liver transplantation [LT]/death, and all-cause mortality) were stratified according to age strata at UC diagnosis. Results: Over 10 years, 1 28 694 incident UC cases were identified (annualised incidence/100, 000 population: 23.8 in 2006; rising to 25.1 in 2015). Of this group, 2124 were diagnosed with PSC at some point (incidence in 2006 and 2015: 0.29 and 0.4, respectively). Observing the UC cohort in entirety, we observed 210 1 st LT (206 in group 2), 9413 individuals who came to colectomy, 1, 208 CRC cases, and 11 177 pt. deaths. The leading cause of mortality was coronary disease (1%) in group 1; whereas liver-related death (5.9%), cholangiocarcinoma (4.6%) and CRC (1%) predominated in group 2. The incidence rate ([IR]/1000-pt.yrs.) was greater in the UC/PSC group for colectomy (17.3 vs 13.7), CRC (5.6 vs 1.5), LT/death (38.5 vs 15.1), and all cause mortality (26.4 vs 15.1); p<0.001 for all. Time-dependent Cox regression validated the negative impact of PSC onset for each endpoint (time-dependent adjusted hazard ratio: 1.62, 3.31, 2.47 and 1.62, respectively; p<0.001 for all). Compared to UC alone, the standardised incidence ratio (SIR) for CRC was greatest in UC/PSC of young presenting age (<40 y.); a 7-fold increase (figure 1A ). This contrasted to pts. diagnosed above age 40 (SIR ~4). Although absolute mortality rate was elevated in older ages (figure 1B) it was in young pts. with UC/PSC that the contrast vs UC alone was most evident for 5 year. (1.6% vs 0.4%) and 10 year. survival (3.6% vs 0.6%); a 4 and 6-fold increase, respectively. Indeed, standardised mortality (SMR) was the greatest for patients diagnosed age < 40 years., and plateaued with older age at diagnosis (figure 1C ). Conclusion: In pts. diagnosed aged < 40 years. with UC, development of PSC is associated with 6-fold increase in mortality and 7-fold increased risk of CRC. Within IBD cohorts, those diagnosed at a young age with PSC have a heightened and disproportionate unmet need for life-prolonging therapies.